Ameliorative Potential of Allium cepa Lam. Leaves on Diabetes Induced and Chronic Constriction Injury Induced Neuropathic Pain in Experimental Rats - Khan, Dureshahwar; Mohammed, Mubashir; Upaganlawar, Aman; Upasani, Chandrashekhar D.; Une, Hemant D. (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Neuropathy can be induced in rats by peripheral injuries, depending on compression of complete or a section of sciatic nerve and chemically by Streptozotocin (STZ). Materials and Methods: In the present study neuropathic pain were induced in rats by two methods, chronic constriction injury (surgical model) and STZ (40mg/kg/i.p.) induced diabetes (drug induced model). In both the models, behavioural as well as markers of oxidative stress were studied. Behavioural parameters were tested using vonfrey hair and Randall Selitto analgesiometer whereas biochemical parameter includes glycosylated haemoglobin and markers of oxidative stress. The study was further supported by histopathology of sciatic nerve. Flavonoid rich extract of Allium cepa Lam. leaves was administered at three different doses viz. 25, 50 and 100mg/kg/p.o to the rats with neuropathic pain. Both the models of neuropathic pain showed significant alteration in behavioural as well as oxidative stress parameters. Results: Treatment of Allium cepa leaves extract showed dose dependent improvement in behavioural and biochemical parameters towards normal (p value <0.001, <0.05 and <0.01). The altered histopathological changes in sciatic nerve were also significantly improved as compared to rats with neuropathic pain. Conclusion: The neuroprotective effects of the Allium cepa leaves extract is a virtue of its strong antioxidant activity.
Keywords: Allium cepa; Neuropathy; CCI; Oxidative stress; Sciatic nerve